Three Decades of Advances in Arabinogalactan-Protein Biosynthesis - Silva, Jessy; Ferraz, Ricardo; Dupree, Paul; Showalter, Allan M.; Coimbra, Sílvia (Frontiers in Plant Science, 2020)
Arabinogalactan-proteins (AGPs) are a large, complex and highly diverse class of heavily glycosylated proteins that belong to the family of cell wall hydroxyproline-rich glycoproteins. Approximately 90% of the molecules consist of arabinogalactan polysaccharides, which are composed of arabinose and galactose as major sugars, and minor sugars such as glucuronic acid, fucose and rhamnose. About half of the AGP family members contain a glycosylphosphatidylinositol (GPI) lipid anchor, which allows for an association with the outer leaflet of the plasma membrane. The mysterious AGP family has captivated the attention of plant biologists for several decades. This diverse family of glycoproteins is widely distributed in the plant kingdom, including many algae, where they play fundamental roles in growth and development processes. The journey of AGP biosynthesis begins with the assembly of amino acids into peptide chains of proteins. An N-terminal signal peptide directs AGPs toward the endoplasmic reticulum where proline hydroxylation occurs and a GPI anchor may be added. GPI-anchored AGPs, as well as unanchored AGPs, are then transferred to the Golgi apparatus where extensive glycosylation occurs by the action of a variety glycosyltransferase enzymes. Following glycosylation, AGPs are transported by secretory vesicles to the cell wall or to the extracellular face of the plasma membrane (in the case of GPI-anchored AGPs). GPI-anchored proteins can be released from the plasma membrane into the cell wall by phospholipases. In this review, we present an overview of the accumulated knowledge on AGP biosynthesis over the past three decades. Particular emphasis is placed on the glycosylation of AGPs as the sugar moiety is essential to their function. Recent genetics and genomics approaches have significantly contributed to a broader knowledge of AGP biosynthesis. However, many questions remain to be elucidated in the decades ahead.